A Ciência da Informação e o paradigma holográfico: a utopia de Vannevar Bush - Santos, Nilton Bahlis dos (2005)
This thesis deals with the challenge and the need of building a model to indicate a path allowing the approach of Information in highly complex and open systems like the Internet. The structure of a new model is necessary to enable us to conceive strategies, methods and technologies for processing unlimited amounts of elements establishing the possibility of an infinity of relations. The models and methods created in order to process information works on systems that are different for they are close systems. These systems assume that they relations are defined a priori, pre-determineted and steady and are able to process only a limited number of elements. Applying such technologies in systems like Internet is only possible in very specific situations. This is why traditional approaches can not describe the study of logics, processes and dynamics of com-plex systems. In these systems the possibility of relations and interactivity is infinite